The E-Transport System for the Shipment of Goods in Romania and Poland: A Modern Faustbuch in Digital Fiscal Regulation - Mănescu, Dragoș Mihail (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
This paper aims to provide an overview of the e-Transport System through an ingenious analogy with the Faustian pact envisioned by Johann Wolfgang von Goethe in his tragedy Faust. Additionally, the paper conducts a comparative legal analysis between Romania and selected few other countries that have implemented a similar e-Transport system, with a particular focus on Poland. Moreover, the paper presents a diverse collection of industry examples, crafted to enrich the exploration of fiscal regulations while shedding light on evolving trends and pressing challenges encountered by lawmakers, businesses, and consumers alike. We target both the technological solutions through a holistic view of the industry as well as the regulatory layers of the fiscal system in the field.